Home Sweet Home : Government's Role in Reaching the American Dream - Tsounta, Evridiki (IMF Working Papers; Working Paper ;, 2011)
This paper investigates the role of government intervention in achieving the American dream of homeownership. The study analyzes the role of tax deductions in housing finance, including their impact on homeownership and housing consumption. The role of the Government Sponsored Enterprises in facilitating the creation of a secondary market for mortgage-backed securities is also analyzed as well as the role of the Federal Housing Administration. Cross-country comparisons of how housing is financed in other industrial countries is also provided, emphasizing how other countries have been able to achieve comparable homeownership rates as the United States in a less complicated and fiscally cheaper system. Country experiences of successfully phasing out government intervention are also analyzed.